OUTREACH AND TRAINING ON THE USE OF BOTANICAL PESTICIDES IN SUPPORT OF SUSTAINABLE AGRICULTURE IN SITUBONDO - Rudianto, Rudianto; Safitri, Nova Monica Aulia; Arianto, Pratama Yuli; Darmawan, Muhammad Riza; Fadhil , Martiana Kholila; Putra, Alfian Andhika; Rikarda, Raden Denisio Edwin; Ramadhani, Candra Putri Rizkiyah; Pratama, Dananjaya Endi (Universitas Muhammadiyah Lamongan, 2025)
Botanical pesticides are naturally occurring chemicals derived from plant sources such as leaves, flowers, roots or seeds. This material has the potential as a more environmentally friendly and sustainable alternative to chemical pesticides. In general, residents in Mangaran Village, Mangaran District, Situbondo Regency work as farmers. In controlling pests and plant diseases, chemical pesticides are usually used to overcome them. The negative impact of using chemical pesticides is that pests will become increasingly resistant to the pesticides given, so stronger pesticides are needed the stronger the attacking pests. This resulted in an increasing number of chemicals in the crops that farmers planted which had an impact on the health of both farmers and consumers. The purpose of this socialization regarding vegetable pesticides is to increase knowledge regarding the manufacture of natural pesticides to control pests and diseases in plants. The socialization and training that was carried out received enthusiasm from farmers and those who attended the socialization were 26 farmers represented by each hamlet. The socialization results obtained are encouraging farmers to produce vegetable pesticides and reduce dependence on chemical pesticides